Structural basis of branch site recognition by the human spliceosome - Tholen, Jonas; Razew, Michal; Weis, Felix; Galej, Wojciech P. (Science, 2022)
Recognition of the intron branch site (BS) by the U2 small nuclear ribonucleoprotein (snRNP) is a critical event during spliceosome assembly. In mammals, BS sequences are poorly conserved, and unambiguous intron recognition cannot be achieved solely through a base-pairing mechanism. We isolated human 17S U2 snRNP and reconstituted in vitro its adenosine 5´-triphosphate (ATP)–dependent remodeling and binding to the pre–messenger RNA substrate. We determined a series of high-resolution (2.0 to 2.2 angstrom) structures providing snapshots of the BS selection process. The substrate-bound U2 snRNP shows that SF3B6 stabilizes the BS:U2 snRNA duplex, which could aid binding of introns with poor sequence complementarity. ATP-dependent remodeling uncoupled from substrate binding captures U2 snRNA in a conformation that competes with BS recognition, providing a selection mechanism based on branch helix stability.